Heat Stress-Associated Growth Retardation in the First 1000 Days Is Mitigated by Preconception Nutritional Supplementation. (7th June 2021) - Shankar, Kartik; Ruebel, Meghan; Kemp, Jennifer; Westcott, Jamie; Jambal, Puujee; Borengasser, Sarah; Piccolo, Brian; Ali, Sumera; Saleem, Sarah; Goldenberg, Robert; Hambidge, K Michael; Krebs, Nancy
Abstract: Objectives: Understanding the interactions between nutrition and climate-driven health outcomes is increasingly necessary. Employing data from the Women First trial conducted in Thatta, Pakistan, we examined the interactions between maternal nutritional deficits and heat stress (HS) on birth outcomes. Methods: Women of child-bearing age either consumed a small quantity lipid-based nutrition supplement (sqLNS) prior to conception (Arm 1 ), from 12 wk of gestation until delivery (Arm 2 ); or were not supplemented with sqLNS (Arm 3) . At the Pakistan site, samples sizes with birth outcomes obtained within 48 h of delivery for Arms 1, 2 and 3 were 157, 150 and 138, respectively. Daily maximal air temperatures were used to were compute the average daily maximal temperatures (Tmax ) for each infant over four 90-day windows representing each trimester of gestation and 3 mo preconception. The number of days in each period when the Tmax was > 39°C was computed to assess 'heat stress days'. Results: Linear regression models assessing the associations between heat exposure and outcome variables (gestational age adjusted Z-scores of birth length (LGAZ), birth weight (WGAZ) and head circumference (HCGAZ) revealed a striking negative association of both ambient temperature and HS days in the first trimester on birth length (LGAZ) and head circumference (HCGAZ) (p < 0.005). For each 5°C increase in the Tmax in the first trimester, LGAZ decreased by 0.15 z-scores and HCGAZ decreased by 0.11 z-scores. Heat exposure (Tmax ) in the second trimester also associated with HCGAZ (p = 0.02 and z-score of −0.11 for every 5°C) but not with birth length or birth weight. RNA-sequencing of placenta indicated a robust association of 1 st trimester HS with genes involved in protein targeting to ER, protein biosynthesis, and cytoplasmic translation. Finally, while non-intervention groups (Arms 2 and 3) showed a robust negative association of excessive HS with LGAZ (p < 0.05), preconception intervention with sqLNS (Arm 1) significantly mitigated heat-associated decreases in birth length. Conclusions: These findings indicate that excessive HS in the first trimester is associated with decreased linear growth in utero. Importantly, sqLNS mitigated growth restriction in newborns implicating nutritional status as a driving force in resilience to HS. Funding Sources: Supported by The BMGF and NICHD.